29‐2: Student Paper: Gaze‐Contingent Light Field Rendering for Near‐Eye Displays. Issue 1 (28th June 2021) - Gao, Chen; (Evan) Peng, Yifan; Li, Haifeng; Liu, Xu
Abstract : We implement a gaze‐contingent light field rendering method for near‐eye displays with eye‐tracking. Unlike optimizing the display layers' content to deliver uniform but low spatial resolution over the eye‐box, we constrain the optimization to enable high spatial resolution within the gaze cone directed to the user's eye with real‐time framerates.